Sleep Quality and Patient Satisfaction after Using Ketamine and Local Anesthetic for Supraclavicular Brachial Plexus Block in Patients Undergoing Upper Extremity Surgery - Sappayanon, Pavit (Thai Journal of Anesthesiology, 2021)
Background: The use of supraclavicular brachial plexus block is the effective and popular anesthetic technique in operations for upper extremity. Ketamine has been found to improve the analgesic effects of local anesthetic drugs and increasing sleep efficiency. Objective: aims to assess the sleep quality and patient satisfaction after using ketamine and local anesthetic for supraclavicular brachial plexus block in patients who underwent upper extremity surgery. Methods: This study was a double-blinded randomized controlled trial. Fifty two patients undergoing upper extremity surgery using the supraclavicular brachial plexus block technique were randomly assigned into 2 groups of 26 patients each. All patients received 10 ml of 0.5% bupivacaine and 13 ml of 2% lidocaine with adrenaline (1:200,000) for supraclavicular brachial plexus block. Ketamine 0.5 mg/kg plus normal saline up to 2 ml and Normal saline 2 ml were added to local anesthetics in group K and group C, respectively. The outcome measures included sleep quality score by using consensus sleep diary and satisfaction score. Results: There was no significant difference among group K and group C in the sleep quality score (3.92 vs 3.46) mean difference 0.46 [-0.02, 0.94; p=0.062] and satisfaction score between group K and C (4.48 vs 4.42), mean difference 0.06 [-0.029, 0.40; p=0.743] Conclusion:Adding ketamine to the bupivacaine-lidocaine mixture in supraclavicular brachial plexus block for patients undergoing upper extremity surgery could not improve the sleep quality and patient satisfaction.